Evaluation of antioxidant and cytotoxic activities of aqueous extracts from Donkioporiella mellea mycelia - Mohd Sairi, Anith Mahfuzah (2021)
Lately, people have started consuming vitamins, dietary supplements, functional food and nutraceutical products in their diet regularly as a source of enhancers. The demand for health-improving food and beverage from natural resources has increased. Polypore mushrooms contain various bioactive compounds that have medicinal alternatives. Traditional Chinese medicine and indigenous people have widely used polypore mushrooms as herbal remedies since yesteryears. In Malaysia, only a small number of common polypore mushrooms has been acknowledged for pharmacological value. New local polypore species was discovered namely, Donkioporiella mellea. D. mellea has identical botanical morphology like other polypore mushrooms with medicinal properties. Somehow, no scientific publication has a record on the potential of D. mellea. Polypore has several growth stages in a complete growth cycle like mycelia, pinhead and fruiting body. As other growth stages of mushroom, mycelia have been reported for pharmaceutical potential. Mycelia can be obtained through suspension culture. Suspension culture promises potential advantages of higher mycelial production in a compact space and shorter time with lesser chances of contamination. Mushroom complete media (MCM) is a suspension media used to culture the mycelium of various polypore mushrooms. This media provides a favourable condition for polypore. However, the total production of mycelia is at a low level. The mycelium growth formation depends on carbon (C) and nitrogen (N) as its primary nutrient sources, which play an important role in mycelial production's yield and efficiency. Therefore, some modification of suspension culture was done as an alternative in obtaining higher mycelial biomass accumulation of D. mellea. The suspension culture media was optimised at 22g/L glucose and 3 g/L yeast extract with mycelial production was 8203.33 ± 110.247 mg/L. The antioxidant properties of D. mellea were evaluated through several antioxidant assays; 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging ability, beta-carotene (β-carotene) linoleate model system and cupric-reducing ion capacity (CUPRAC). Each analysis was tested at serial dilution concentration of extract (0.01, 0.02, 0.04, 0.08, 0.16, 0.31, 0.63, 1.25, 2.5, 5 and 10 mg/ml). Hot aqueous extract of D. mellea showed good scavenging activity compared to cold aqueous extract with EC50 values 2.9 ± 1.986 and 3.3 ± 1.326 mg/ml, respectively. Meanwhile, the cold aqueous extract has good antioxidant activity in protecting β-carotene compared to hot aqueous extract with EC50 value 0.31 ± 0.754 and 1.25 ± 0.963 respectively. Both D. mellea extracts showed same CUPRAC ability with CUPRAC value 1.791 ± 0.046 and 1.821 ± 0.053 at 0.08 mg/ml respectively. The biocompatibility of D. mellea and human body was discovered by cytotoxicity test through 3-[4,5-dimethylthiazole-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. The cytotoxicity activity of D. mellea extract was tested on normal human lung fibroblast (MRC5) and human lung carcinoma (A549). The cytotoxic evaluation was done in serial dilution concentration of extracts (1.95, 3.9, 7.8, 15.625, 31.25, 62.5, 125, 250, 500 and 1000 μg/ml). Aqueous extracts of D. mellea exhibited selective cytotoxicity potential with selective index (SI); 8.71 And 3.14 for hot and cold aqueous extract, respectively. Hot and cold aqueous extracts of D. mellea have mild anti-cancer properties against A549 at 500 μg/ml with the percentage of inhibition were 15.67 ± 1.93 and 50.24 ± 2.23 respectively. In general, the findings proved that D. mellea has potential and more biological evaluation needed for stimulating research advancement in mycological studies.